Hadith as Pedagogical Discourse: Compilation Criticism and the Formation of Fiqh–Sufi Praxis in Buya Mansur's Hidāyat al-Ṭālibīn - Gusnanda Eljambaki; Sri Chalida; Sri Handayana; Aidil Alfin (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Scholarly attention to local Islamic textual traditions has grown considerably, yet the pedagogical dimensions of regionally produced hadith literature remain underexplored. This article investigates the pedagogical function of hadith in Hidāyat al-Ṭālibīn fī Bayān Aḥādīṡ Sayyid al-Mursalīn (Guidance for Seekers in Explaining the Hadiths of the Leader of the Messengers), a local hadith text composed by Buya Manshur within the intellectual tradition of Persatuan Tarbiyah Islamiyah (PERTI) in Minangkabau. Employing qualitative textual analysis and compilation criticism, the study examines how the selection, arrangement, and explanation of 82 hadiths across eight thematic chapters construct a coherent educational discourse that integrates hadith, fiqh, and practical spirituality. The findings reveal a deliberate progressive structure, moving from epistemological foundations (hadith scholarship, revelation, faith, and religious knowledge) toward embodied ritual practice (ablution, ritual bath, menstruation, and dry ablution). This structure indicates that fiqh is not simply a repository of legal rulings but a pedagogically ordered framework for cultivating religious subjectivity. Significantly, the foregrounding of ritual purity demonstrates that bodily discipline functions as a formative site for spiritual awareness and worship readiness. The article argues that Hidāyat al-Ṭālibīn represents a distinctive local model of Islamic pedagogy in which hadith operates simultaneously as normative proof-text and as an instrument for shaping Muslim selfhood. This finding contributes to broader discussions on indigenous Islamic educational traditions and the vernacular development of hadith scholarship in the Malay-Indonesian world.